PERENCANAAN SETTING DIRECTIONAL GROUND RELAY (DGR) UNTUK GANGGUAN SATU FASA KE TANAH DI SALURAN 150 KV DOUBLE CIRCUIT GIS PESANGGARAN – GI NUSA DUA - Ganggas B Maulana Idham; I Gede Dyana Arjana; I Wayan Arta Wijaya (Program Studi Teknik Elektro UNUD, 2021)
The single phase to ground fault on the 150 kV transmission line GIS Pesanggaran –Nusa Dua Substation has a high fault impedance so that the distance relay as anauxiliary safety device cannot detect the disturbance. Directional Ground Relay (DGR)was chosen as an auxiliary protection relay to secure the system from single phase toground faults. Installation of auxiliary protection relays requires planning and relaysetting steps to obtain Iset, TMS and trip time. The calculations that have been carriedout get the results of DGR setting with a pickup current range of 0.0522 – 0.0722 A.DGR will work after 2.297 seconds if the differential relay as the main protection relaydoes not work or fails and the distance relay as a backup protection does not succeed insecuring a single phase fault to ground as well.